Radiation-Induced Esophagitis is Mitigated by Soy Isoflavones - Fountain, Matthew D.; Abernathy, Lisa M.; Lonardo, Fulvio; Rothstein, Shoshana E.; Dominello, Michael M.; Yunker, Christopher K.; Chen, Wei; Gadgeel, Shirish; Joiner, Michael C.; Hillman, Gilda G. (Frontiers in Oncology, 2016)
Introduction: Lung cancer patients receiving radiotherapy present with acute esophagitis and chronic fibrosis, as a result of radiation injury to esophageal tissues. We have shown that soy isoflavones alleviate pneumonitis and fibrosis caused by radiation toxicity to normal lung. The effect of soy isoflavones on esophagitis histopathological changes induced by radiation was investigated. Methods: C57BL/6 mice were treated with 10 Gy or 25 Gy single thoracic irradiation and soy isoflavones for up to 16 weeks. Damage to esophageal tissues was assessed by H&E, Masson’s Trichrome and Ki-67 staining at 1, 4, 10, 16 weeks after radiation. The effects on smooth muscle cells and leukocyte infiltration were determined by immunohistochemistry using anti-αSMA and anti-CD45 respectively. Results: Radiation caused thickening of esophageal tissue layers that was significantly reduced by soy isoflavones. Major radiation alterations included hypertrophy of basal cells in mucosal epithelium and damage to smooth muscle cells in muscularis mucosae as well as disruption of collagen fibers in lamina propria connective tissue with leukocyte infiltration. These effects were observed as early as one week after radiation and were more pronounced with a higher dose of 25 Gy. Soy isoflavones limited the extent of tissue damage induced by radiation both at 10 and 25 Gy. Conclusions: Soy isoflavones have a radioprotective effect on the esophagus, mitigating the early and late effects of radiation injury in several esophagus tissue layers. Soy could be administered with radiotherapy to decrease the incidence and severity of esophagitis in lung cancer patients receiving thoracic radiation therapy.